KURIKULUM DAN MATERI PENDIDIKAN ISLAM - Gaffar, Irfan Abd. (State Institute of Islamic Studies (IAIN) Palu, 2006)
Curriculum serves as a set of subjects to teach. It functions as a guideline for teachers in educating their students. Therefore, it isvery important to design a curriculum that fits the society’s needs. Nowadays, curriculum of Islamic education faces some problems emerging in society. The reason is that society is very critical in choosing which institution of education it is going to enter for. Based on this, in referring to design of curriculum of Islamic education, a designer should try his best to design a curriculum that really fits society’s needs on education. Kata Kunci: kurikulum, pendidikan Islam